Towards a Fairer Future: An Activist Model of Black Girl Leadership. Issue 2 (1st June 2020) - Cook, Courtney
Abstract: In the study on which this article is based, I examine the correlation between the number of Black girls in leadership programs and the number of Black female leaders in nonprofit organizations. I carried out research on Black girl leadership to understand the shortcomings of programs meant to teach Black girls appropriate leadership skills and I conducted interviews with female leaders to determine the hurdles faced by Black women trying to obtain leadership roles in the nonprofit sector. My findings show that there is a disconnect between Black and white women in leadership roles and that impediments for Black women affect leadership prospects for Black girls. This article is a call to create an activist model that supports the professional trajectories of Black girls.